Implementing a Facilitated Black Admissions Process in a Canadian Physiotherapy Programme. - Spadoni, Gregory F.; Wojkowski, Sarah; Smith-Turchyn, Jenna; Stratford, Paul W.; Osuji, Ebuka (Physiotherapy Canada, 2026)
Purpose: To report on the development, implementation, and evaluation of a facilitated Black admissions programme (FBAP) in a Canadian physiotherapy programme in 2023. Method: We observed and reported on the development and application process of a FBAP in a Master of Science Physiotherapy [MSc(PT)] programme, and the characteristics and results of applicants who applied through the FBAP and compared their interview experience with the conventional stream of applicants in the MSc(PT) programme. We summarized the candidate data from the streams using descriptive statistics and then compared the stream's interview score means and the evaluator scores between and within streams by calculating intraclass correlation coefficients and standard errors of measurements. Results: Our analysis revealed the mean scores of the FBAP were significantly higher than those of the conventional stream (p =  0.018). There was no difference in the correlation between sub-GPA and interview scores for the two streams. In addition, the comparison of the interrater reliability of the FBAP (ICC: 0.76; 95% CI: 0.43, 0.90) and the conventional stream (ICC: 0.82; 95% CI: 0.79, 0.84), demonstrated alignment with no significant difference. Conclusions: In 2023, McMaster University successfully implemented the first iteration of the FBAP stream and fulfilled a vision that began in 2021 to increase the diversity of underrepresented minorities and decrease historical barriers for Black applicants in their MSc(PT) admissions processes.